2021
DOI: 10.1186/s12864-021-08129-5
|View full text |Cite
|
Sign up to set email alerts
|

CoRe: a robustly benchmarked R package for identifying core-fitness genes in genome-wide pooled CRISPR-Cas9 screens

Abstract: Background CRISPR-Cas9 genome-wide screens are being increasingly performed, allowing systematic explorations of cancer dependencies at unprecedented accuracy and scale. One of the major computational challenges when analysing data derived from such screens is to identify genes that are essential for cell survival invariantly across tissues, conditions, and genomic-contexts (core-fitness genes), and to distinguish them from context-specific essential genes. This is of paramount importance to as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 86 publications
(104 reference statements)
0
22
0
Order By: Relevance
“…So far, we have analyzed gene inhibition sensitivity from CRISPR screens as a quantitative trait. However, in many cases the results of CRISPR screens are binarized, such that genes are deemed to be either essential or non-essential for survival 37,39,40 . Genes which are essential in a specific context might then be considered as suitable therapeutic targets.…”
Section: Resultsmentioning
confidence: 99%
“…So far, we have analyzed gene inhibition sensitivity from CRISPR screens as a quantitative trait. However, in many cases the results of CRISPR screens are binarized, such that genes are deemed to be either essential or non-essential for survival 37,39,40 . Genes which are essential in a specific context might then be considered as suitable therapeutic targets.…”
Section: Resultsmentioning
confidence: 99%
“…We also examined the gene expression profiles of these core essential genes and observed that the 314 genes at the intersection of the three approaches have higher median gene expression compared to genes that are uniquely core essential in each approach (median log2(TPM) 6.3 versus 5.1 for new common specific genes, 5.4 for CEGV2 and 4.7 for Sanger specific genes; Figure 3C ). An expanded comparison of the newly identified common essentials with the more recently defined core essential genes using CoRe AdaM ( 44 ) and CENtools ( 45 ) approaches showing the overlap between the datasets is shown in Supplementary Figure S6 . These observations are consistent with an increased false negative rate among essential genes with moderate levels of mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…They highlighted the opportunity to generate new models for rare and paediatric cancer, where there is a large unmet clinical need, and to map their dependencies [23]. Furthermore, they showcased studies using co-essentiality analysis to describe novel gene function [9], integration of pharmacological and CRISPR data to understand drug mode of action [10], opportunities to identify drug combinations [24], to interpret cancer gene mutations and gene fusions [25], and to define human essential genes [26], amongst other possible applications.…”
Section: Covered Topics Talks and Discussionmentioning
confidence: 99%